Dramatic Structure in Teuku Umar Theater Show in Meulaboh City, West Aceh Regency - Radhiah, Aisyatur; Jazuli, Muhammad; Wadyio, Wadyio (Catharsis, 2019)
Mappadendang traditional ceremony is a traditional ceremony that is held every year by Bugis society as an expression of gratitude for the abundance of the results of the crop. This traditional ceremony is usually combined with the Padendang dance, which is a traditional dance of the Bugis people, especially in Abbanuangnge Village, Soppeng Regency. It is derived from the word "Pa" which means the actor, "dendang" which means rhythm. Besides as a series of Mappadendang traditional ceremonies, this dance also functions as entertainment. The uniqueness of this dance lies in its attractive movements using properties called as rice pestle (stick). Besides that, it was supported by the sound of the collapsed pestle carried out by the mothers and accompanied by drum instruments. The purpose of this study is to analyze the aesthetics of Padendang dance at Mappadendang traditional ceremony of the Bugis society in Soppeng Regency. The method used in this study is a qualitative method. Data collection techniques are observation, interview and document study. The data validity technique uses triangulation techniques and data analysis techniques that follow the stages of interactive model analysis. The results of the Padendang dance research are three parts of the movement: the beginning of the movement, mappakaraja, the main part of the movement, Sere Padendang, the harvest and the final part mappatabe’ movement. The aesthetic findings of Padendang dance there are three aesthetic elements that exist in the Padendang dance, namely the shape / form of motion of the Padendang dance, the quality / content / message conveyed in the Padendang dance, and the performance / talent or skill possessed by the dancers.